2012
DOI: 10.1029/2010wr009275
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of water resources evolution in the highly water‐stressed Hai River Basin of China

Abstract: .[1] Many observations and studies have shown that water resources amount in the Hai River Basin decreased significantly over the last half of the twentieth century. This study attempts to attribute the observed changes in the water resources amount in the basin over a 40 year period to different factors, including natural climate variability, climate change induced by anthropogenic forcing of greenhouse gas emissions (referred to as anthropogenic forcing hereafter), and local human activity. First, the tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Bao et al (2012) proposed that climate variability was the major driving factor in the Taolinkou catchment, and human activities were the main driving factor in the Zhangjiafen and the Guantai catchment of the Haihe River Basin. Jia et al (2012) indicated that local human activity is the main factor for the changes in the water resources during the period of 1961-2000, and it accounted for about 60 % of the changes. In addition, Lei et al (2014) suggested that climate induced runoff in Haihe River Basin exhibits a decreasing trend since 1960, and changes in precipitation, solar radiation, air temperature, and wind speed accounts for 56, 14, 13, and 5 % of the overall decrease in annual runoff, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Bao et al (2012) proposed that climate variability was the major driving factor in the Taolinkou catchment, and human activities were the main driving factor in the Zhangjiafen and the Guantai catchment of the Haihe River Basin. Jia et al (2012) indicated that local human activity is the main factor for the changes in the water resources during the period of 1961-2000, and it accounted for about 60 % of the changes. In addition, Lei et al (2014) suggested that climate induced runoff in Haihe River Basin exhibits a decreasing trend since 1960, and changes in precipitation, solar radiation, air temperature, and wind speed accounts for 56, 14, 13, and 5 % of the overall decrease in annual runoff, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Since the groundwater is overexploited, local land water resources are declining rapidly, and an extreme water crisis has emerged in the Basin (Xu et al, 2004;Yang and Tian, 2009;Liang et al, 2011;Jia et al, 2012). Rivers at least 4000 km long, which account for about 40% of the total length of all rivers in the Basin, have become seasonal rivers.…”
Section: Study Domainmentioning
confidence: 99%
“…For example, Jia et al (2012) employed a fingerprintbased method to attribute observed changes in water resource amounts in the Hai catchment, China, to local human activity, rather than climate variability. Vorogushyn and Merz (2013) showed that an important contribution to detected increasing trends in observed flood time series along the Rhine is attributable to extensive river training.…”
Section: Introductionmentioning
confidence: 99%